Kepribadian Tokoh Utama dalam Novel "Hidup ini Brengsek dan Aku Dipaksa Menikmatinya" karya Puthut E. A. vs Gindring Wasted: The Personality of The Main Character in "Hidup ini Brengsek dan Aku Dipaksa Menikmatinya" by Puthut E. A. vs Sleight of Wasted - Ichsani, Noor Sahid; Normalita, Aulia (Kibas Cenderawasih, 2023)
In life, one's problems will always arise both internally and externally. This study picks up Puthut's E.A. vs. Gindring Wasted novel titled Life Is a Jerk, and I'm Forced to Enjoy It. The approach used is literary psychology. Research methods are qualitative descriptive. The source of the data is the novel Life Is A Jerk, and I'm Forced to Enjoy It. Research data is in the form of phrases or sentences from the character "I" in the novel Life Is Jerk, and I Am Forced to Enjoy It. Data analysis uses Freud's personality theory (Id, Ego, and Super Ego), Lickona theory (Moral knowledge, moral feelings, and moral behavior), an interactive analysis model from Miles and Huberman.  The results of this study are, 1) The personality of the main character has an honest personality, vindictive, does not want to filter the various offers he gets first, cowardly, lazy to mince words, and likes to forgive. 2) The educational value that can be taken from the novel Life Is Jerk, and I Am Forced to Enjoy It Puthut E.A. vs Gindring Wasted's work that is, obedient, full of sympathy, and the habit to do deeds according to the values and norms that apply by not judging someone.